1996
DOI: 10.1080/026990596123945
|View full text |Cite
|
Sign up to set email alerts
|

Outcome following traumatic brain injury: a comparison between 2 and 5 years after injury

Abstract: This study examined long-term outcome in traumatically brain-injured individuals following discharge from a comprehensive rehabilitation programme. Of 254 traumatic brain injury (TBI) patients reviewed at 2 years, 103 have been followed up at 5 years using a structured interview format detailing neurological symptoms, mobility, independence in ADL, productivity status, relationship issues, communication and the presence of cognitive, behavioural and emotional changes. Visual difficulties, headache and fatigue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
241
2
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(276 citation statements)
references
References 3 publications
12
241
2
9
Order By: Relevance
“…Van der Naalt and colleagues (1999) noted that at 1 month post injury, 57% of the sample reported fatigue, dropping to 45% at 6 months and one year [1]. Another study reported that 73% of individuals continue to experience fatigue as a chronic problem 5 years post-injury [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Van der Naalt and colleagues (1999) noted that at 1 month post injury, 57% of the sample reported fatigue, dropping to 45% at 6 months and one year [1]. Another study reported that 73% of individuals continue to experience fatigue as a chronic problem 5 years post-injury [3].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, studies have shown that the presence of PTBIF may prevent return to work [9]. PTBIF has not been found to be associated with age or injury severity [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…The variability of the period taken into consideration could perhaps explain why some authors reported time since injury as an important predictor [21] and other authors did not [17,19]. In TBI patients, the functional recovery is typically slow and occurs during the whole year after brain injury and sometimes beyond [75][76][77][78]. Consequently, results of studies adopting a 3-or 6-month follow-up do not generalize to the majority of TBI patients.…”
Section: Introductionmentioning
confidence: 99%
“…Even those deemed to have made a good recovery often have residual psychological or emotional deficits which prevent them from returning to pre-injury levels of functioning [6][7][8]. However, several researchers suggest that good long-term adjustment after brain injury is achievable, even after severe TBI [9][10][11].…”
Section: Introductionmentioning
confidence: 99%